Applying Problem-Based Classroom Learning to Assist Students in increase Students’ Speaking Skill: English - Musdalifah Musdalifah; Annisa Kurnia Asri; Raudatul Jannah (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2024)
The purpose of this study was to elucidate how SMPN 3 Asembagus class VIII students could benefit from problem-based learning interactions in order to improve their speaking skills in 2023–2024. This study used classroom action research (CAR) as its research approach. They have an extremely small vocabulary, which makes it difficult for them to speak English. As a result, students require an additional teaching strategy known as problem-based learning (PBL) to develop their speaking skills. The objective of this research was to determine how to use problem-based learning as a teaching strategy to improve the speaking skills of students and their academic achievement. The action research was carried out in some manner. These procedures included the pre-test, post-test, and the cycle that starts with planning, acting, observing, and reflecting. Methods for gathering data include testing, documentation, and observation. This method was used in exams, in-class activities, observations, documentation, and student evaluations of both themselves and their peers. The study's findings indicated that there had been a quantitative improvement in the students' speaking skills. Additionally, students engaged more fully in the oral instruction and learning process. In summary, the eighth grade students in SMPN 3 Asembagus were able to speak English more fluently and effectively thanks to the great and efficient use of problem-based learning. As a result, the students' speaking skills improved, as is clear from the preceding result, and this strategy contributed favorably to the improvement of speaking skills. This approach is useful for making the process of teaching students to speak English more pleasurable.